Some hydrodynamic aspects of gas-liquid fluidized beds - Ahmad Tariq Jameel; Shaukat Ali (2001)
Hydrodynamic characteristics of up-ward flow gas-liquid fluidized bed for air-waterglass bead system was investigated using a 19 cm dameter perspex column. The gas and liquid superficial velocities in the range of 0.0-1.1 cm/s sand 0.0-3.64 cm/s respectively, and glass beads of average diameters 2.50, 2.56 and 3.71 mm were studied. The effect of gas and liquid velocities and that of particle size on the quality of fluidization is related to various phase hold-ups in the bed. The gas holdup increased with increasing gas velocity and it decreased with the rise in liquid velocity whereas liquid holdup followed just the opposite trend. Howeve1; the bed porosity increased linearly with increase in gas and liquid velocities. These observations largely confirmed to the general trend reported in the literature. The particle size distribution was found to have significant influence on hydrodynamic parameters. The empirical correlations (from literature) for predicting bed porosity and liquid holdup were found to lie within 10 to 20 percent deviations from our experimental results. One such correlation was modified to closely fit our experimental data. The investigation validates the existing data for scale up to large .scale, as the bed diameter studied was closer to pilot scale than most of the works reported in the literature